Schema theory’s immediate impact on college students’ Chinese reading comprehension - Huang, Tsui-Feng; Chou, Sheng-Chieh; Liao, Anna (International Journal of Evaluation and Research in Education (IJERE), 2024)
Studies show that there is an increase of college students who prefer reading short summaries rather than long complex texts containing knowledge or theory. Thus, this study focuses on improving first-year students’ reading comprehension in Chinese courses by observing the effectiveness of teaching reading lessons in Chinese courses with the curriculum designed based on “schema theory”. The selected reading materials are extensive texts with certain knowledge or theories. For evaluation purposes, the reading test questions uses the same measure of reading proficiency levels of program for international student assessment (PISA) to assess learners’ reading comprehension, contextual reasoning, integration, and analysis abilities more accurately. By comparing the results and discrepancies of the pre- and post-assessment, the preliminary research found that the teaching practice and curriculum designed based on schema theory effectively improves learners' reading scores and instill habits to increase their tendency to reach a deeper understanding of the reading material. This finding demonstrates the effectiveness of applying schema theory to reading lessons; resulting in potential of immediate and enhanced levels of comprehension.